Performance of binary exponential backoff CSMA in WiFi and optimal routing in mobile ad hoc networks - Philippe Jacquet; Amina Meraihi Naimi; Georgios Rodolakis (Discrete Mathematics & Theoretical Computer Science, 2005)
In this paper we show that the CSMA IEEE 802.11 protocol (Wifi) provides packet access delays asymptotics in power law. This very feature allows us to specify optimal routing via polynomial algorithm while the general case is NP-hard.